2019
DOI: 10.1097/phm.0000000000001108
|View full text |Cite
|
Sign up to set email alerts
|

Fit4SurgeryTV At-home Prehabilitation for Frail Older Patients Planned for Colorectal Cancer Surgery

Abstract: Objective The preoperative phase is a potential window of opportunity. Although frail elderly patients are known to be more prone to postoperative complications, they are often not considered capable of accomplishing a full prehabilitation program. The aim of this study was to assess the feasibility of Fit4SurgeryTV, an athome prehabilitation program specifically designed for frail elderly with colorectal cancer (CRC). Design The Fit4SurgeryTV program consisted of a daily elderly-adapted computer-supported str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 25 publications
2
58
0
1
Order By: Relevance
“…The partial list of fascial plane blocks includes transversus abdominis plane, 6 pectoral I and II, 7 serratus anterior plane, 8,9 erector spinae plane, 10 rectus sheath, 11 quadratus lumborum, 12 and transversalis fascia blocks. 13 The fundamental problem, however, is that the notion that truncal blocks can achieve the same reliable efficacy as ultrasound-guided regional anaesthesia of the limbs neglects the essence of the latter's success: the precise administration of local anaesthetics as close as possible to the relevant nerve structures. Although some blocks of the trunk do involve nerves coming into direct contact with the local anaesthetic (e.g.…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…The partial list of fascial plane blocks includes transversus abdominis plane, 6 pectoral I and II, 7 serratus anterior plane, 8,9 erector spinae plane, 10 rectus sheath, 11 quadratus lumborum, 12 and transversalis fascia blocks. 13 The fundamental problem, however, is that the notion that truncal blocks can achieve the same reliable efficacy as ultrasound-guided regional anaesthesia of the limbs neglects the essence of the latter's success: the precise administration of local anaesthetics as close as possible to the relevant nerve structures. Although some blocks of the trunk do involve nerves coming into direct contact with the local anaesthetic (e.g.…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…Videoconferencing cannot replace essential hospital visits nevertheless can complement the delivery of health services and is largely accepted as an effective and non-inferior alternative to face-to-face therapy in the delivery of both postsurgical rehabilitation [14,15] and prehabilitation [17,[19][20][21]. It has further proven to be feasible and effective to deliver nutritional and psychological counseling [16,22].…”
mentioning
confidence: 99%
“…Although the optimal prehabilitation program is different based on a variety of factors for each patient, several authors have developed in-home prehabilitation models, and preliminary data have shown decreased length of stay, more likely discharge to home, and decreased costs. 24 , 25 Some combination of office-based and home-based prehabilitation is likely the optimal program currently, but this is rapidly evolving and should be patient-centered.…”
Section: Prehabilitation For the Colorectal Surgery Patientmentioning
confidence: 99%